Principles of teaching professionally-oriented foreign language in virtual reality - Polina G. Labzina; Maksim V. Gureev; Maksim E. Zhabin; Evgenij I. Novalov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the study of the principles of training and advantages of virtual reality technology in the process of learning foreign languages for specific purposes in comparison with traditional educational forms. The potentialities of virtual reality as an ideal educational environment are pointed out. This idea lets us formulate the principles of teaching foreign languages such as facilitation, autonomy of students’ activity, interactivity, professional orientation, multimodal presentation of educational information, independent educational activity. The implementation of the teaching principles mentioned above by means of virtual reality, makes it possible to create educational conditions that meet the requirements of the time and contribute to increasing the effectiveness of teaching not only foreign languages but also other disciplines. This approach helps develop professional qualities that ensure the successful performance of specific functions related to the future professional activity and, consequently, and are in demand on the modern labor market.When analyzing the potential of virtual reality, it is revealed that the main component of the virtual reality program is an accurately generated space / room which lets the learner immerse into the professional sphere during the process of study. The emphasis is on the multimodal nature of virtual reality, which optimizes the learning process through the multidimensional transmission and perception of information. The interactive actions in virtual reality are considered a facilitating factor in teaching a professionally oriented foreign language. This factor optimizes the independent and autonomous activity of students and ensures their involvement in active communicative activity and creates a high level of motivation for mastering the subject. Simulation of the professional interaction is contrasted with the traditional class atmosphere in order to avoid the subject-object relationship model. Based on the results of practical work of specialists in the field of information technologies, and also based on our own experience in creating a virtual reality program, the authors come to the conclusion that the introduction of virtual interaction into the educational process will improve the effectiveness of the results of students' educational activity in the process of mastering a professional foreign language.